2016
DOI: 10.3892/mmr.2016.5573
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of paeonol on methyl-4-phenyl-1,2,3,6-tetrahydropyridine/probenecid-induced Parkinson's disease in mice

Abstract: Paeonol is a major phenolic compound of the Chinese herb, Cortex Moutan, and is known for its antioxidant, anti-inflammatory and antitumor properties. The present study was designed to investigate the therapeutic potential and underlying mechanisms of paeonol on a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine/probenecid (MPTP/p)-induced mouse model of Parkinson's disease (PD). MPTP (25 mg/kg), followed by probenecid (250 mg/kg), was administered via i.p. injection for five consecutive days to induce the mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 54 publications
4
23
0
Order By: Relevance
“…injection of TAK242 (3 mg/kg; TLR4 antagonist) 1 hour before the LPS injection (LPS 1 TAK242). The doses of LPS and paeonol were determined from the literature (Hsieh et al, 2006;Lee et al, 2013;Shi et al, 2016) and preliminary data (Supplemental Fig. 1, A and B), which showed that 20 mg/kg paeonol improved relaxation in response to the endothelium-dependent vasodilator acetylcholine in mice treated with LPS (15 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…injection of TAK242 (3 mg/kg; TLR4 antagonist) 1 hour before the LPS injection (LPS 1 TAK242). The doses of LPS and paeonol were determined from the literature (Hsieh et al, 2006;Lee et al, 2013;Shi et al, 2016) and preliminary data (Supplemental Fig. 1, A and B), which showed that 20 mg/kg paeonol improved relaxation in response to the endothelium-dependent vasodilator acetylcholine in mice treated with LPS (15 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Blocking microglial activation by minocycline also protects the nigrostriatal dopaminergic pathway against MPTP model, suggesting that microglial activation plays a crucial role in the pathogenesis of PD ( 95 ). The treatment with paeonol decreased MPTP/p-induced oxidative stress and neuroinflammation through the increase of the brain-derived neurotrophic factor (BDNF), one of the most critical NFs in the physiology of CNS ( 96 ).…”
Section: Inflammation In Pd: Cause or Consequence Of The Disease?mentioning
confidence: 99%
“…Cordycepin, resveratrol, hesperetin rendered up-regulation of the level and activity of antioxidants such as, SOD, GPx, CAT, GSH in 6-OHDA induced PD models ( Khan et al, 2010 ; Kiasalari et al, 2016 ; Olatunji et al, 2016 ). Treatment with paeonol improved the MPTP-induced the oxidative stress, as determined by enhancing the activity levels of SOD, CAT, and GSH in the mouse PD model ( Shi et al, 2016 ). Gastrodin, the major active component in the Gastrodia elata , has been demonstrated to have many pharmacological effects, such as antioxidative and neuroprotective properties.…”
Section: Natural Anti-oxidant Molecules and Their Applications In Pd mentioning
confidence: 99%